IMPLEMENTASI UU NO.23 TAHUN 2007 TENTANG PERKERETAAPIAN (STUDI KASUS TENTANG PEMERIKSAAN DAN PENELITIAN KECELAKAAN KERETA API DI KANTOR PUSAT PT. KAI (PERSERO) BANDUNG) - Mega Fitria Ayuningputri; Slamet Santoso; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The train is one of the mass transport that demanded by the public. PT.KAI(Persero) is a sole operator of organizing railway in Indonesia. The Vision and Mission of PT.KAI(Persero) is providing service and safety to the public as a train users. In 2007-2011 there was a train accident with the same factor from the train itself. Based on Law No.23 Tahun 2007 about Railways, there was a discussion of investigation and research of train accidents ,in which the discussion was intended to minimize the railway accidents. Implementation of transparency investigation reports and research train accident done by PT.KAI (Persero) deficient, because PT.KAI (Persero) give information is still common, simple, and temporary to public, the description of the results of investigation reports and research train accident PT.KAI (Persero) should be valid and must announce it to public in accordance with the contents of the Law No.23 Tahun 2007 of the Railways.